Resuscitation using less fluid has no negative impact on hydration status in children with moderate sized scalds: a prospective single-centre UK study. Issue 7 (November 2017) - Hollén, Linda; Coy, Karen; Day, Andrew; Young, Amber
Highlights: Little evidence exists regarding correct volumes of fluid in children with burns. Serum sodium was comparable between patients given less fluid and those given more. Urine output was similar in patients given less fluid and those given more fluid. Children remain adequately hydrated at 24 h after-burn with reduced fluids. Abstract: Background: After a burn, optimal fluid resuscitation is critical for positive patient outcome. Although national guidelines advocate using resuscitation fluids of 4 mL per kg body weight and percent body surface area (%BSA) for paediatric burns of >10% BSA, evidence in adults suggest that such volumes lead to over-resuscitation and related complications. Our aim was to investigate whether children managed with biosynthetic dressings (Biobrane™) and reduced fluid volumes remain well hydrated, as determined by clinical and laboratory parameters. Methods: At a single UK Burn Centre, children with scalds of 10–19%BSA managed with Biobrane were given 80% maintenance fluids and no formal burn resuscitation (permissive hypovolaemia [PH] group). Urine output (UO), serum sodium, urea, and creatinine were used as 24 h markers of hydration and concentrations compared to those in a patient cohort treated within the same centre when traditional resuscitation was used (TR group). Results: Serum sodium concentrations and UO in the PH group were similar to those in the TR group (median sodium: PH = 136, TR = 136, P = 1.00; median UO: PH = 1.5, TR = 1.8, P = 0.25). Urea concentrations were lower and creatinine concentrations higher in the TR group compared to the PH group (median urea: PH = 3.2, TR = 2.3, P = 0.04; median creatinine: PH = 21, TR = 30, P < 0.001). A higher proportion of TR patients than PH patients fell outside the reference ranges for urea (61% vs. 23%; P = 0.04) and creatinine (44% vs. 8%; P = 0.03). Conclusion: Based on markers of hydration, children with moderate-sized scalds managed with Biobrane can be safely managed with less fluid.